Proximate composition of tilapia feed formulated with varying levels of moringa (Moringa oleifera) leaf flour - Talunga, Junianto; Kreckhoff, Reni Lucia; Lintang, Rosita A. J.; Sambali, Hariyani; Pangemanan, Novie Pankie Lukas; Salaki, Christina Leta; Sumilat, Deiske Adeliene (AQUATIC SCIENCE & MANAGEMENT, 2025)
This study evaluated the effect of incorporating moringa leaf flour (Moringa oleifera) at varying concentrations into feed formulations on the proximate composition of tilapia (Oreochromis niloticus) feed. Five experimental treatments were tested, with moringa leaf flour inclusion levels of 0% (control), 10%, 20%, 30%, and 40%. A proximate analysis was conducted to determine moisture, ash, fat, protein, and crude fiber content. The results indicated that only the control feed (0%) and the feed containing 10% moringa leaf flour met the required protein standards for formulated feed, at 30% and 25%, respectively. Feeds with higher inclusion levels had protein content below the minimum threshold. The lowest crude fiber content (14.98%) was recorded in the 10% treatment, which was lower than that of the control. Ash, fat, and moisture contents remained relatively stable across all treatments and within acceptable ranges for fish feed. The formulation with 10% moringa leaf flour provided the optimal nutritional profile, delivering adequate protein (25%) and the lowest crude fiber (14.98%), thereby meeting nutritional requirements without compromising digestibility. Based on proximate analysis, moringa leaf flour shows potential as an efficient alternative feed ingredient for tilapia aquaculture.